Mapping the landscape of talent management research in higher education: a bibliometric analysis - Razlina Razali; Muhammad Aiman Arifin; Latisha Asmaak Shafie; Farah Lina Azizan; Mohd Azlan Mohd Ishak (Cogent Business & Management, 2024)
Research on talent management (TM) in higher education has witnessed a positive development in recent years, following the rising recognition of TM as a key strategy for higher learning institutions to achieve competitive advantage and sustainable performance. However, a comprehensive review of TM using bibliometric analysis that focused on TM research in higher education has not been published. Following this gap, the present study used quantitative bibliometric approaches to statistically and objectively explore research publication patterns of TM in higher education. VoSviewer and Bibliometrix R-package were used to analyse data retrieved from the Scopus database. This analysis involved seven indicators such as highly cited papers, prominent authors, co-authorship patterns among countries, influential journals and countries, thematic mapping, emerging trends, and bibliographic coupling. Results showed that TM in higher education is an evolving topic, with contributions from scholars since 2006. It emerged from this study that topics such as leadership, recruitment, talent attraction, talent development, talent retention, and employee engagement are inherent to TM in higher education. It is important to study the development of TM research in higher education and its characteristics as this type of analysis is still scarce in the literature. The present study contributes to the literature by providing the evolution of this research field as well as helping scholars shape future work in this field.Our paper presents findings and discussions on the evolution of talent management (TM) research in higher education, elicited using bibliometric approaches. This study is motivated by past scholars and practitioners who have recognized the importance of TM as a key strategy for organizations to achieve a strategic advantage and sustainable performance. This article contributes to the understanding of current developments in TM research in the higher education context. Discussions in this article can facilitate readers in thinking about ways to improve research and practices of TM in higher education, as well as in their respective contexts. Our bibliometric analyses, which have been explained in a straightforward manner, can be adapted by future scholars who are interested in studying the evolution of research studies in their respective areas.
Keywords: 650; Talent management; higher education; bibliometric analysis; Scopus